2022
DOI: 10.3390/en15239133
|View full text |Cite
|
Sign up to set email alerts
|

Research Status and Development Trend of Unmanned Driving Technology in Coal Mine Transportation

Maosen Wang,
Jiusheng Bao,
Xiaoming Yuan
et al.

Abstract: Unmanned driving technology has always been one focus of mine smart transportation, which is a crucial component of smart mines. However, the descriptions of both the intelligent transportation system and its industrial application are not comprehensive. In order to have an all-encompassing and comprehensive understanding of both the intelligent coal mine transportation system and its industrial application with the intelligent system, this paper summarizes and analyzes the current research status of unmanned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…(1) Each factor in the criterion layer is compared separately in each element (scheme) in the scheme layer. Their importance is scored using the numbers in the interval (1,9) to form a judgment matrix. After the consistency ratio test C × R = λ max −n (n−1)R×I < 0.1 is met, the weight direction w i = (w 1 , w 2 , .…”
Section: Determination Of Assessment Index Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Each factor in the criterion layer is compared separately in each element (scheme) in the scheme layer. Their importance is scored using the numbers in the interval (1,9) to form a judgment matrix. After the consistency ratio test C × R = λ max −n (n−1)R×I < 0.1 is met, the weight direction w i = (w 1 , w 2 , .…”
Section: Determination Of Assessment Index Weightsmentioning
confidence: 99%
“…The majority of these accidents are caused by fire-induced gas explosions, with the severity of death reaching more than nine people per fire accident, and the severity of death in all other accidents is less than that of fire accidents, so coal mines need to pay sufficient attention to fire [4][5][6]. In recent years, China's coal enterprises also generally pay attention to the prevention of coal mine fire accidents, and the construction of a major disaster prevention and protection system for China's coal enterprises has gone through five stages: passive prevention, traditional empirical prevention pre-prevention post-prevention, systematic prevention and protection, and systematic scientific management [7][8][9]. At present, most of China's coal enterprises are still in the fourth stage, and the emergency rescue construction of China's coal enterprises still has problems in all aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In June 2021, the National Energy Administration and the National Mine Safety Supervision Bureau collaborated to release the "Guidelines for the Intelligent Construction of Coal Mines". These guidelines aim to facilitate the systematic and organized implementation of intelligent construction practices across the coal mining industry [3]. The auxiliary transportation vehicles usually employed in underground coal mines are regarded as one of the most frequently utilized means of transportation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Transportation issues are also examined in the context of ensuring the safety of mining crews, including in the studies by Tu et al 2023 [13], Li et al (2022) [14], Fabiano et al (2014) [15], and Thakur (2019) [16]. This trend also includes advanced studies on unmanned transportation carried out in the spirit of smart technologies, as demonstrated by Wang et al (2022) [17]. Transportation also appears as a subject of consideration for individual links of mining production, such as in Yuan et al 2022 [18], Krauze et al (2020) [19], and Szewerda et al (2021) [20].…”
Section: Introductionmentioning
confidence: 99%